Editors' Note: Cognitive-Driven Activities of Daily Living Impairment as a Predictor for Dementia in Parkinson Disease: A Longitudinal Cohort Study. (21st February 2023) - Lewis, Ariane; Ganesh, Aravind; Galetta, Steven
Abstract : In "Cognitive-Driven Activities of Daily Living Impairment as a Predictor for Dementia in Parkinson Disease: A Longitudinal Cohort Study, " Becker et al. report that while 40% of 268 patients with Parkinson disease (PD) had mild cognitive impairment (MCI) at baseline, of 164 patients who completed follow-up after 3.78 ± 0.84 years, 33% had MCI and 10% had dementia. Patients in this study were evaluated using the Functional Activities Questionnaire (FAQ) to differentiate cognitive and motor contributions to impairment in performance of instrumental activities of daily living (IADL). Kasten questions how the results of the FAQ compared with results of the Montreal Cognitive Assessment (MoCA) and whether these scores could be used interchangeably. Dr. Kasten also cites a prior study that found that the Unified Parkinson Disease Rating Scale was moderately correlated with the MoCA. Becker reports there was a weak to moderate correlation between FAQ and MoCA scores at both baseline and follow-up. However, although there is some overlap between these assessments, Becker does not believe they should be used interchangeably because MoCA measures general cognition while the FAQ measures cognitive contributions to IADL impairment. This exchange highlights important methodological considerations when screening for cognitive decline in PD.